Impact of Body Mass Index on mortality in Swiss hospital patients with ST-elevation myocardial infarction: does an obesity paradox exist? (Swiss Medical Weekly, 2014)
BACKGROUND: The obesity paradox refers to the phenomenon that obese patients seem to have a better outcome than normal weight patients in a variety of disease conditions. The aim of this study was to investigate the impact of Body Mass Index (BMI) on mortality in patients with ST-elevation myocardial infarction (STEMI) who underwent percutaneous coronary intervention (PCI). METHODS: Between January 2005 and July 2012, the Swiss AMIS Plus registry enrolled 6,938 patients with acute STEMI who underwent PCI. These patients were stratified into 5 BMI groups according to the classification system of the World Health Organisation. The odds for in-hospital mortality according to BMI groups were analysed using logistic regression with normal weight patients as the reference. RESULTS: Crude in-hospital mortality rates showed a U-shaped distribution between BMI groups, with the lowest mortality in obese class I patients (2.0%) and the highest mortality in underweight patients (9.0%). The odds for in-hospital mortality were significantly lower for obese class I (OR 0.56; 95% CI 0.35–0.91) and significantly higher for underweight patients (OR 2.72; 95% CI 1.14–6.48) compared to the normal weight group and odds ratios showed a U-shaped distribution. After adjustment for covariates, the odds ratios maintained a U-shape distribution albeit the differences between BMI groups were no longer significant. CONCLUSION: This study showed that the lower crude in-hospital mortality of obese class I patients can be partly explained by lower age and lower co-morbidity rates. However, further studies are needed to investigate favourable factors associated with class I obesity.